Interference suppression with physical-layer network coding and MIMO for multi-way channels - Brás, F. (2014)
Orthogonal techniques (such as TDMA – time division multiple access) are traditionally used when a set of terminals wants to exchange data and a relay is required when wireless terminals cannot communicate directly. This paper proposes two schemes to address multi-way channels when a set of terminals wants to exchange data. Both proposed schemes consist of a first phase based on virtual MIMO with lattice reduction-aided (LRA) detection at the relay, establishing a multiple access channel (MAC). Two new strategies are then proposed for the second (multicast) phase; one for single antenna terminals and another for multiple-input multiple-output (MIMO) terminals. The second strategy achieves interference suppression by successively combining physical layer network coding and MIMO detection (with LRA detectors also at the terminals). The paper assesses a 3 terminals network with a relay for which a TDMA-based scheme would require 6 time-slots, while the proposed strategy for MIMO terminals is able to exchange the information between all terminals using 2 time-slots only. This latter scheme is easily scalable to a higher number of terminals, and always able to accomplish the exchange of messages between all of them in just 2 time-slots, although limited by the number of antennas that the terminals can fit and also the MIMO processing complexity they can afford.